IMMUNOHISTOCHEMICAL DETECTION OF FIBRONECTIN IN HUMAN THYMUS-COMPARISON BETWEEN GROUPS OF DIFFERENT AGES - Ali, Shafqat; Minhas, Liaqat Ali; Hameed, Waqas; Arshad, Muhamad (Pakistan Journal of Physiology, 2009)
Objective: To compare distribution of fibronectin content in various parts of human thymus between groups of different ages using immunohistochemistry. Design: Comparative study. Place and duration of study: The study was carried out in Anatomy Department, Army Medical College Rawalpindi from Oct 2007 to Dec 2007. Material and methods: Forty specimens from tissue sections of human thymus were separated into two groups with 20 specimens in each group: Group A consisted of specimens from the patients of 1-25 years and Group B of specimens from patients beyond 40 years. These specimens were fixed in 10% formalin solution and processed for paraffin embedding. Five micron thick sections were made. Immunohistochemical staining was utilized to localize fibronectin in various regions of human thymus (capsule, connective tissue between lobules, cortex, medulla and areas around blood vessels). Results: Statistically highly significant difference was found between two groups with a marked increase in the distribution of fibronectin content of the thymic capsule, the connective tissue between the lobules, areas around the blood vessels, and the medulla and cortex of the thymus in Group B compared to Group A. Conclusion: The fibronectin content in human thymus in its various regions shows a marked increase in aged people as compared to younger ones.